PENGEMBANGAN MEDIA PEMBELAJARAN CROCLE MATH UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS - Arini, Adinda Yudhistira Putri; Kartika, Era Dewi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
This study aims to develop Crocle Math learning media to improve the understanding of mathematical concepts in junior high school mathematics learning that is valid, practical and effective. The research method used in this study is research and development (R&D). The research design used is Borg & Gall. The subjects in this study were media experts, material experts and VII grade students of SMP Negeri 2 Dau One Roof. The instruments used in this study were validation sheets to determine the validity of the media, student response questionnaires to determine the practicality of the media, and mathematical concept understanding test tests to determine the effectiveness of the media. The results of this study indicate that the results of the Crocle Math media development receive a valid category based on the validation by material experts with a percentage of 88% and media experts with a percentage of 96% with both in the very good category. In addition, based on the practicality of the media from the results of student response questionnaires get a percentage of 77% with a practical category and the effectiveness of the media from the results of the mathematical concept understanding test test results that students' concept understanding in learning mathematics has increased based on the scores they get. The results of both tests get an n-gain score of 0.63 with a moderate category. Therefore, Crocle Math media is declared as valid, practical and effective media for learning mathematics.